Impact of a multidomain lifestyle intervention on regional spontaneous brain activity - Moon, So Young; Shin, Seong A.; Jeong, Jee Hyang; Hong, Chang Hyung; Park, Yoo Kyoung; Na, Hae Ri; Song, Hong-Sun; Park, Hee Kyung; Choi, Muncheong; Lee, Sun Min; Chun, Buong-O; Lee, Jong-Min; et al. (Frontiers in Aging Neuroscience, 2022)
In the SoUth Korean study to PrEvent cognitive impaiRment and protect BRAIN health through lifestyle intervention in at-risk older adults (SUPERBRAIN), we evaluated the impact of multidomain lifestyle intervention on regional homogeneity (ReHo) in resting-state functional brain magnetic resonance imaging (MRI) data. Of 152 participants aged 60–79 years without dementia assigned to either facility-based multidomain intervention (FMI), home-based MI, or controls, we analyzed 56 scanned MRIs at baseline and 24 weeks. ReHo values from regions with significant longitudinal changes were compared between the intervention and control groups and their correlations with the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) or serum brain-derived neurotrophic factor (BDNF) were evaluated. ReHo values in the left medial orbitofrontal gyrus and right superior parietal lobule were increased (p=0.021, correlated positively with serum BDNF changes [r=0.504, p=0.047]) and decreased (p=0.021, correlated negatively with changes in the total [r=-0.509, p=0.044] and attention [r=-0.562, p=0.023] RBANS), respectively, in the participants assigned to the FMI group than those of the controls. Our results suggest that facility-based group preventive strategies may have cognitive benefits through neuroplastic changes in functional processing circuits in the brain areas which play a crucial role in the adaptive learning and internally directed cognition.